Sosialisasi Disiplin Positif Pada Program Pesantren Ramah Anak Terhadap Kesehatan Mental Santri - Abdulloh Muhamad Al-kaff; Sutrisno Sutrisno; Suwadi Suwadi (LPPM-IAI Hidayatullah Batam, 2026)
This community service the implementation of positive discipline in the Child-Friendly Islamic Boarding School (Pesantren Ramah Anak/PRA) program and its impact on students' mental health. The paradigm shift from authoritarian punishment-based discipline to humanistic and restorative approaches has become imperative, given that traditional disciplinary practices may cause psychological trauma and increase students' anxiety. This community service uses the Participatory Action Research Method, to identify practices, challenges, and psychological impacts of positive discipline implementation in Islamic boarding schools. The findings reveal that core positive discipline practices include dialogical techniques (musyawarah/deliberation), individual coaching based on mutual respect, and participatory rule formulation. Main implementation challenges include cultural resistance to traditional ta'dib concepts and teacher workload. Successful adaptation strategies encompass recontextualizing positive discipline within Islamic values such as syura (consultation) and rahmah (compassion), as well as involving senior students as agents of change. Significant impacts on students' mental health include increased sense of safety, decreased anxiety and stress levels, and development of emotional regulation skills and empathy. This community service affirms that PRA success must be measured not only by the absence of physical violence but also by the quality of psychological environment that supports children's resilience.